Prognostic factors and survival study in high-grade glioma in a hospital in Lima, Peru: Factores pronóstico de supervivencia en adultos por gliomas de alto grado en un hospital de Lima, Perú - Méndez-Aguilar, Paul (2020)
Introduction: Gliomas are primary tumors of the central nervous system. They are classifiedfrom grade I-IV, with high grade III and IV being the most frequent and with poor prognosis. Objective: To determine the prognostic factors of survival in patients with high-gradegliomas in a hospital in Lima, Peru. Methods: The medical records with high-grade gliomafrom 2010-2014 were retrospectively reviewed, ten variables were analyzed with Kaplan-Meier and Log Rank survival graphs and the Cox regression model. Results: Out of a total of278 patients with high-grade gliomas, 136 were men and 142 women. The analysis of Progression-Free Survival (SLP) had a range of 5.6-80.3 (median 22.7) and the analysis ofoverall survival (PS) had a range of 4-83.2 (median 26, 2 months. The overall survival for theIV grade tumor was 15.7 months (95% CI 14.2-17.1); the III degree was 38.4 months (95%CI 35.8-40.9). The grade (PS: HR 15; SLP: HR 25.1); surgical treatment (PS: HR 0.6; SLP:HR 0.49), age (PS: HR 1.47; SLP: HR 1.7), adjuvant treatment (PS: HR 0.6; SLP: HR 0 , 58)and karnofsky (PS: HR 0.7) were correlated; while the Karnofsky for SLP does not (P =0.146). Conclusion: age, functional status, surgical treatment, adjuvant treatment, and tumorgrade are prognostic factors for PS. In contrast, for SLP the prognostic factors were age,surgical treatment, adjuvant treatment, and tumor grade.